The Connection between Arabic and Western Culture in the Rise of Populism - Fadlil Munawwar Manshur (Humaniora, 2019)
This article discusses the rise of populism in Arabic and Western cultures as well as the connection between them. This study shows that populism in the Arab and Western world have several common characteristics: resistance against the mainstream, xenophobia, isolation, intolerance, hostility towards strangers, extremism, radicalism, anti-multiculturalism, and anti-globalization. The rise of populism has aﬀected Arabic and Western cultures, as well as their interactions. Because of populism, Western culture’s views of the outside world, strangers, immigrants, and Islam has changed significantly. Western culture, inﬂuenced by populism, tend to be intolerant, isolated, xenophobic, and lack trust in multiculturalism. Meanwhile, populism in Arabic culture tends to be more anti-Western, anti-capitalist, and anti-liberalist. With the rise of populism, relations between these two cultural entities have become colored by tension, distrust, suspicion, and xenophobia.